The Influence of Reading Habit on Reading Comprehension by EFL Papuan Students - Nur Ainy Retyanasari (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
This study aims to describe the level of reading habits of the sixth semester EFL students of English Study Program IAIN Fattahul Muluk Papua and to find out to the extent of the level reading habits has an influence on students' reading comprehension. This research applies descriptive quantitative method using descriptive statistical analysis and simple linear regression by SPSS. The number of research subject was 25 EFL students of the sixth semester. The instrument of the research to collect data is a questionnaire consisting of 18 statements about reading habits and 10 statements about reading comprehension. The results showed that: (1) The level of reading habits of the sixth semester EFL students is considered good with the highest average score on the indicators of motivation, effort and interest in reading; (2) The calculations of simple linear regression show that there is an influence given by reading habits on EFL students' reading comprehension, where it can be concluded that the better level of reading habits, also the better their reading comprehension will be. With these results, it was suggested that students must be aware of the importance of having reading habit in order to achieve reading comprehension.